Open Cavity Controllable Dual-Wavelength Hybrid Raman-Erbium Random Fiber Laser - Zainol Abidin N.H.; Yao L.K.; Abu Bakar M.H.; Tamchek N.; Mahdi M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Erbium; Fiber lasers; Stimulated Raman scattering; Bidirectional pumping; Dual wavelength; Erbium doped fibers; Gain medium; Laser-based; Lasing peaks; Random fibers; Single lasers; Fibers